PROFESSIONAL AND SOCIAL SELF-DETERMINATION OF YOUTH UNDER CONDITIONS OF THE MODERNIZATION OF HIGHER EDUCATION - Yu. Belikova, Natalia; U. Ponomareva, Elena; V. Kotlyarova, Victoria; V. Yushina, Svetlana; I. Abbasova, Leviza; T. Latysheva, Anna (Gênero & Direito, 2020)
The authors emphasize that the modernization of higher education has a certain effect on the professional and social self-determination of youth. Based on the analysis of secondary empirical data, the authors note that the reform of the education system in Russia entailed the outflow of young people who are getting higher education today. Despite these indicators, the youth who aspire to get higher education have the opportunity to get international mobility, access to online education, and internships at large enterprises, which allows them to build their life and professional strategies more clearly and competently.